A conceptual framework on learner’s attitude toward using AI chatbot based on TAM Model in English classroom - Linh, Pham My; Wu, Ting-Ting (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
This paper presents a conceptual framework for investigating students' attitudes toward the use of an AI chatbot in an English classroom. It integrates the foundational constructs of the TAM model, such as perceived usefulness, perceived ease of use, attitude toward use, and behavioral intention to use, within the context of an AI chatbot application used in an English classroom. The framework hypothesizes that students' perceptions of the AI chatbot's usefulness and usability will significantly impact their attitudes toward its incorporation into the English classroom. To validate the framework, empirical data will be collected using surveys and interviews with English language learners from various educational institutions in future studies. The findings can inform the development of strategies and interventions designed to promote positive attitudes and acceptance of AI technology in language education.